Embarazo y parto en los cronistas de los siglos XVI-XVII - Chávez, Fabiola (1997)
In this article we present documents that narrate the beliefs and practices regarding a part of the reproductive cycle of women: pregnancy and childbirth. Many of these beliefs and practices are still in force, which may indicate a cultural continuity from Inca or pre-Inca times to date.